Eukaryote-Like Serine/Threonine Kinases and Phosphatases in Bacteria - Pereira, Sandro F. F. (American Society for Microbiology (ASM), 2011)
Summary: Genomic studies have revealed the presence of Ser/Thr kinases and phosphatases in many bacterial species, although their physiological roles have largely been unclear. Here we review bacterial Ser/Thr kinases (eSTKs) that show homology in their catalytic domains to eukaryotic Ser/Thr kinases and their partner phosphatases (eSTPs) that are homologous to eukaryotic phosphatases. We first discuss insights into the enzymatic mechanism of eSTK activation derived from structural studies on both the ligand-binding and catalytic domains. We then turn our attention to the identified substrates of eSTKs and eSTPs for a number of species and to the implications of these findings for understanding their physiological roles in these organisms.